ATH-1105, a small-molecule positive modulator of the neurotrophic HGF system, is neuroprotective, preserves neuromotor function, and extends survival in preclinical models of ALS - Berthiaume, Andrée-Anne; Reda, Sherif M.; Kleist, Kayla N.; Setti, Sharay E.; Wu, Wei; Johnston, Jewel L.; Taylor, Robert W.; Stein, Liana R.; Moebius, Hans J.; Church, Kevin J. (Frontiers in Neuroscience, 2024)
Introduction Amyotrophic lateral sclerosis (ALS), a progressive and fatal neurodegenerative disorder, primarily affects the motor neurons of the brain and spinal cord. Like other neurodegenerative conditions, ongoing pathological processes such as increased inflammation, excitotoxicity, and protein accumulation contribute to neuronal death. Hepatocyte growth factor (HGF) signaling through the MET receptor promotes pro-survival, anti-apoptotic, and anti-inflammatory effects in multiple cell types, including the neurons and support cells of the nervous system. This pleiotropic system is therefore a potential therapeutic target for treatment of neurodegenerative disorders such as ALS. Here, we test the effects of ATH-1105, a small-molecule positive modulator of the HGF signaling system, in preclinical models of ALS. Methods In vitro, the impact of ATH-1105 on HGF-mediated signaling was assessed via phosphorylation assays for MET, extracellular signal–regulated kinase (ERK), and protein kinase B (AKT). Neuroprotective effects of ATH-1105 were evaluated in rat primary neuron models including spinal motor neurons, motor neuron-astrocyte cocultures, and motor neuron-human muscle cocultures. The anti-inflammatory effects of ATH-1105 were evaluated in microglia- and macrophage-like cell systems exposed to lipopolysaccharide (LPS). In vivo, the impact of daily oral treatment with ATH-1105 was evaluated in Prp-TDP43A315T hemizygous transgenic ALS mice. Results In vitro, ATH-1105 augmented phosphorylation of MET, ERK, and AKT. ATH-1105 attenuated glutamate-mediated excitotoxicity in primary motor neurons and motor neuron- astrocyte cocultures, and had protective effects on motor neurons and neuromuscular junctions in motor neuron-muscle cocultures. ATH-1105 mitigated LPS-induced inflammation in microglia- and macrophage-like cell systems. In vivo, ATH-1105 treatment resulted in improved motor and nerve function, sciatic nerve axon and myelin integrity, and survival in ALS mice. Treatment with ATH-1105 also led to reductions in levels of plasma biomarkers of inflammation and neurodegeneration, along with decreased pathological protein accumulation (phospho-TDP-43) in the sciatic nerve. Additionally, both early intervention (treatment initiation at 1 month of age) and delayed intervention (treatment initiation at 2 months of age) with ATH-1105 produced benefits in this preclinical model of ALS. Discussion The consistent neuroprotective and anti-inflammatory effects demonstrated by ATH-1105 preclinically provide a compelling rationale for therapeutic interventions that leverage the positive modulation of the HGF pathway as a treatment for ALS.